(untitled) (International journal of artificial intelligence, 2026)
This paper explores the significance of an axiologically-informed pedagogical approach in fostering personal and professional growth within the educational context. The axiological approach emphasizes the importance of not only imparting knowledge but also cultivating spiritual, moral, and professional values among learners. It encompasses strategies for promoting personal growth, self-reflection, professional identity development, and social responsibility through a scientific framework.